Laboratory Methods Of Studying Children With Facial Developmental Faults - Muxsinova L.A (Genius Journals, 2024)
Facial malformation in children is not only a medical but also a social problem all over the world. At the end of the 20th century, over the past two decades, there was a 2-fold increase in the frequency of birth of children with this pathology. In the structure of mortality of children in perinatal and early childhood, congenital defects occupy a significant place. And congenital orofascial defects are among the five most common intrauterine malformations.
Keywords: malformations of the face; laboratory tests; children